PERAN BANK INDONESIA DALAM MENSTABILKAN PEREKONOMIAN DAN JUMLAH UANG BEREDAR MELALUI KEBIJAKAN MONETER - Ai, Ai Nurendah (Lobi, 2024)
This research is motivated by the economic conditions and the amount of money circulating in Indonesia in terms of the last five years, what policies will be issued by Bank Indonesia. This research aims to analyze the role of Bank Indonesia in stabilizing the economy and the amount of money in circulation through monetary policy. Object This research is an Indonesian bank using descriptive qualitative research. This research uses a descriptive method with a qualitative approach. This data was obtained by obtaining information and using secondary data by obtaining information through the official website of Bank Indonesia and the Central Statistics Agency and this research shows that the monetary policy implemented by Bank Indonesia has a significant role in maintaining economic stability and the amount of money in circulation.